Evaluasi Program Pendidikan Inklusif di SMPN 015 Kota Tanjungpinang - Desy Pitrianengsy; Nafisah Aulia Rani (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2022)
Inclusive Education policy in Permendiknas No. 70 2009 is defined as an education system that provides opportunities for all students with disabilities and potential intelligence or special talents to participate in education or learning in the educational environment together with students in general. One of them in Tanjungpinang that has implemented an inclusive education program is SMPN 015 with a mild disability classification. This school has implemented this program from 2019 until now. This school has accepted 13 students from 2019-2022. In its implementation, SMPN 015 Tanjungpinang still has several obstacles and obstacles due to the lack of advice and infrastructure as well as human resources, but in dealing with these obstacles, SMPN 015 Tanjungpinang carries out strategies such as making picket schedules and collaborating with students and parents. SMPN 015 Tanjungpinang also hopes that related agencies will pay more attention to this inclusive education program. This type of research is descriptive with a qualitative approach using indicators from the CIPP evaluation model proposed by Stufflebeam (1971).